Jaderné palivo v provozních podmínkách - Konopová, Tamara (Vysoké učení technické v Brně. Fakulta elektrotechniky a komunikačních technologií, 2016)
Tato práce se zabývá problematikou jaderného paliva. V práci je nejprve představeno palivo v realizaci pro tlakovodní reaktory a je probrána jeho výroba včetně představení společností, zabývající se výrobou tohoto paliva. Následně je probrána problematika jaderného paliva za provozu, se zaměřením na vyhořívající absorbátory a jevy v palivu. V další části je proveden výpočet absorbátoru a srovnání gadolinia jako vyhořívajícího absorbátoru a erbia jako vyhořívajícího absorbátoru.

This thesis deals with the issue of nuclear fuel. Firstly, the problem of nuclear fuel in the implementation for pressurized water reactors is presented. Production of nuclear fuel is introduced, which includes the performance of companies engaged in the production of this fuel. Secondly, problems of nuclear fuel during operation, focusing on burnable absorbers and phenomena in the fuel burnup are discussed. Lastly, the calculation is carried out and gadolinium as a burnable absorber is compared with erbium as a burnable absorber.
Nuclear Fuel in Operational Conditions
Keywords: PWR; VVER; jaderné palivo; výroba jaderného paliva; jevy v palivu; vyhořívající absorbátory; gadolinium; erbium; PWR; VVER; nuclear fuel; nuclear fuel cycle; phenomena of fuel burnup; burnable absorber; gadolinium; erbium